2012
DOI: 10.1097/mbc.0b013e3283570846
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of platelet aggregation by chlorogenic acid via cAMP and cGMP-dependent manner

Abstract: In this study, we investigated the effect of chlorogenic acid, a phenolic acid, on collagen (10 μg/ml)-stimulated platelet aggregation. Chlorogenic acid dose-dependently inhibited collagen-induced platelet aggregation, and suppressed the production of thromboxane A2 (TXA2), an intracellular Ca-agonist as an aggregation-inducing autacoidal molecule, which was associated with the strong inhibition of cyclooxygenase (COX)-1 in platelet microsomes having cytochrome c reductase activity. In addition, chlorogenic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…CE-WIB801C more increased exclusively cAMP than cGMP on collagen-induced platelet aggregation, which trend is as well as those by phenolic compounds such as epigallocatechin-3-gallate (Ok et al ., 2012), chlorogenic acid (Cho et al ., 2012), and caffeic acid (Lee et al ., 2014) that cAMP-dependently inhibited [Ca 2+ ] i mobilization in collagen-activated platelets. The levels of intracellular cAMP and cGMP are regulated by the balance between cyclic nucleotide-producing enzymes, adenylate/guanylate cyclases, and hydrolyzing enzymes, cAMP/cGMP phosphodiesterases (PDEs).…”
Section: Discussionmentioning
confidence: 99%
“…CE-WIB801C more increased exclusively cAMP than cGMP on collagen-induced platelet aggregation, which trend is as well as those by phenolic compounds such as epigallocatechin-3-gallate (Ok et al ., 2012), chlorogenic acid (Cho et al ., 2012), and caffeic acid (Lee et al ., 2014) that cAMP-dependently inhibited [Ca 2+ ] i mobilization in collagen-activated platelets. The levels of intracellular cAMP and cGMP are regulated by the balance between cyclic nucleotide-producing enzymes, adenylate/guanylate cyclases, and hydrolyzing enzymes, cAMP/cGMP phosphodiesterases (PDEs).…”
Section: Discussionmentioning
confidence: 99%
“…This is associated with the activation of A-kinase or G-kinase, since these enzymes block Ca 2+ mobilization by phosphorylating IP3R to inhibit the generation of the TXA2 substrate, AA 18,40) . CAFA (50 μM) increased the cAMP level more so than the cGMP level in the collagen-induced platelet aggregation, a trend that is also observed with respect to phenolic compounds, such as EGCG 11) and chlorogenic acid 36) . The levels of cAMP and cGMP in platelets are regulated by A B lets) achieved by collagen only (Fig.…”
Section: mentioning
confidence: 69%
“…2) was associated with the inhibition of the microsomal COX-1 activity ( Table 1). In a previous study, we reported that chlorogenic acid (50 μM), an analogue of CAFA, inhibits the COX-1 activity in platelets to 69.7% compared with that observed (52.5±2.5 pmoL/ min/protein-mg) in the controls in vitro 36) . In addition, the COX-1 inhibitor aspirin (50 μM) inhibited the COX-1 activity in platelets to 11.3% compared with that observed (1.59 nmoL/min/protein-mg) in the controls in vitro 12) .…”
Section: mentioning
confidence: 99%
“…Thus, a compound that can inhibit TXA 2 production-associated enzymes (COX-1 or TXAS), TXA 2 production or TXA 2 action has a potential application as an anti-thrombotic agent (Clutton et al , 2001). Phytochemicals such as ginseng saponin (Lee et al , 2012), chlorogenic acid (Cho et al , 2012), caffedymine (Park, 2007) and sanguinarine (Jeng et al , 2007) inhibited TXA 2 production in agonists-stimulated platelets, which were involved in inhibition of COX-1 activity. These previous reports are accord with fact that the inhibition of agonists-induced platelet aggregation is supported by inhibition of COX-1 rather than TXAS (Lewis and Watts, 1982; Jang et al , 2002).…”
Section: Discussionmentioning
confidence: 99%